Short-term blood pressure variability and outcomes in non-dialysis chronic kidney disease - Wang, Ge; Ma, Kai; Ma, Zhilan; Guo, Xiaoyan; Wang, Yan; Ma, Lan; Qi, Chenchen; Li, Yan; Zhou, Xiaoling (Frontiers in Medicine, 2022)
Background. Blood pressure variability (BPV) is associated with cardiovascular and all-cause mortality, and has been demonstrated in dialysis patients, but has been poorly studied and remains controversial in non-dialysis chronic kidney disease (CKD) patients. We investigated the effect of short-term BPV on prognosis in this population. Methods. A total of 245 stage 1-4 CKD patients with 24-hour ambulatory blood pressure recordings were recruited. BPV was evaluated by standard deviation, coefficient of variation, and variation independent of the mean, respectively. All subjects were followed up to the composite end-point event or until January 15, 2020. Patients were divided into two groups based on 24-hour median variation independent of the mean, and demographics, laboratory indicators and echocardiogram results were compared. Logistic regression was used to analyze the risk factors for increased BPV. Multivariate Cox regression and Kaplan-Meier survival analysis were used to explore the relationship between BPV and renal prognosis and major cardiovascular events. Results. The mean age was 42.07 ± 12.66 years, with 141 males (57.55%). Multivariate Logistic regression analysis showed that high BMI (OR 1.110, P = 0.017), hyperkalemia (OR 2.227, P = 0.040), increased left ventricular end-diastolic diameter (OR 1.103, P = 0.010) and hypertension (OR 2.525, P = 0.002) were independent risk factors for high BPV. Kaplan-Meier survival analysis showed that renal and cardiovascular outcomes were better in the low BPV group than in the high BPV group (P = 0.006; P = 0.002). After adjusting for age, sex and traditional kidney related risk factors, BPV were not independently associated with renal outcomes. High BPV (HR 4.662, P = 0.017) was the main independent risk factor for major cardiovascular events in CKD. Conclusions. In non-dialysis CKD, short-term BPV was associated with major cardiovascular disease but not renal progression. BMI, hypertension, potassium balance, and left ventricular end-diastolic diameter influenced short-term BPV.